CHARACTERISTICS OF THE NOISE STABILITY OF RADIO COMMUNICATION SYSTEMS WITH FREQUENSY HOPING - I. I. Skib; A. V. Martsinovich; E. L. Kreidik; V. A. Cherdyntsev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Typical block diagrams of communication systems with frequency hopping are considered. Synthesis of algorithm and the processing device of signals with frequency hopping in fading channels are resulted. The comparative evaluation of noise stability of receiving signals with frequency hopping is given.